2019
DOI: 10.1111/jvp.12833
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and body weight gain on enrofloxacin pharmacokinetics in turkeys—Allometric approach to dose optimization

Abstract: Enrofloxacin is a concentration‐dependent antimicrobial used in bacterial infections in poultry. During a few months of a turkey's life, pharmacokinetics of drugs undergoes substantial changes which may compromise their efficacy due to variability in internal exposure (measured by area under the concentration–time curve, AUC). The aim of this study was to describe the effects of age on the pharmacokinetics of a single intravenous (i.v.) and oral administration of enrofloxacin at a dose of 10 mg/kg to turkeys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 44 publications
3
33
1
Order By: Relevance
“…Enrofloxacin is indicated clinically for the treatment of gastroenteric, respiratory, urogenital and skin infections in pigs, calves, cattle, and poultry [ 5 , 6 ]. Several kinds of research were carried out for pharmacokinetics pattern of enrofloxacin in different species including pigs [ 7 ], rabbits [ 8 ], sheep [ 9 , 10 ], goats [ 11 ], horses [ 12 , 13 ], poultry [ 5 , 6 , 14 , 15 ], turkey [ 16 ] and Japanese quail [ 4 ] under normal conditions. Moreover, it has been reported that pharmacokinetics of enrofloxacin is altered when concurrent administration with albendazole in calves [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enrofloxacin is indicated clinically for the treatment of gastroenteric, respiratory, urogenital and skin infections in pigs, calves, cattle, and poultry [ 5 , 6 ]. Several kinds of research were carried out for pharmacokinetics pattern of enrofloxacin in different species including pigs [ 7 ], rabbits [ 8 ], sheep [ 9 , 10 ], goats [ 11 ], horses [ 12 , 13 ], poultry [ 5 , 6 , 14 , 15 ], turkey [ 16 ] and Japanese quail [ 4 ] under normal conditions. Moreover, it has been reported that pharmacokinetics of enrofloxacin is altered when concurrent administration with albendazole in calves [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of scientific evidence supporting the role of growth in the change of antimicrobial PK in broiler chickens and turkeys is extensive [ 2 , 3 , 4 , 5 , 6 , 7 ]. It is clear that the internal exposure to antimicrobials in these birds changes according to the power law relation to BW [ 20 , 21 , 22 ] and may be responsible for the suboptimal response to treatment in young individuals [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a significant age-dependent decrease in the capability of the clearing organs to eliminate drugs is seen. Indeed, the difference between the total body clearance (CL) in different age groups may be even three-fold as shown for metronidazole [ 2 ] or enrofloxacin [ 4 ] in turkeys. Significant age-dependent drop in CL has also been described for florfenicol in broilers [ 3 ] as well as for amoxicillin [ 5 ], doxycycline [ 6 ] and sodium salicylate [ 7 ] in turkeys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations